Learners' Learning Readiness as a Foundation for Achieving Learning Success - Pairin Pairin (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This article aims to provide an overview of learners 'learning readiness, which includes the relationship of motivation to learning readiness, as well as the relationship of parents' attention to learning readiness. The method used in this study is the study of library materials, which are related to learning readiness. Reading material is limited only in the last ten years. The results of the study indicate that learning success is largely determined by physical, psychological, and initial knowledge about the subject to be faced. Therefore, students must ensure their readiness comprehensively. This responsibility must start from the family environment, then by the school through the conditioning of a conducive learning environment. Psychologically, learning readiness can be influenced by motivation, both internally and externally. Students should not be left trapped in external impulses that are temporary in following learning. Instead, students are directed to the deepest awareness of their main mission in participating in learning. Sociologically, the role of the family through high attention can also be an important factor in achieving learning success. Keywords: Learning Readiness, Motivation, Attention